2017
DOI: 10.1002/ldr.2673
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution and Management Zones for Sulphur and Micronutrients in Shiwalik Himalayan Region of India

Abstract: Agricultural land degradation due to nutrient deficiencies is a threat to agricultural sustainability. As nutrients availability is influenced by soil heterogeneity, climatic conditions and anthropogenic activities; hence, delineation of nutrient management zones (MZs) based on spatial variability could be an effective management option at regional scale. Thus, the present study was carried out to delineate MZs in the Shiwalik Himalayan region of India by capturing spatial variability of soil properties and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 69 publications
(96 reference statements)
10
42
0
Order By: Relevance
“…In soils of northern Ethiopia, low (for pH) and medium variability (for SOC and available Fe) were reported (Tesfahunegn et al, ). Moderate variability for available Zn, Fe, Cu, and Mn was recorded by Wang, Wu, Liu, Huang, and Fang () in China's paddy growing soils and by Shukla et al (), Shukla et al () in Indian TGP and SHR soils. However, Foroughifar, Jafarzadeh, Torabi, Pakpour, and Miransari () recorded high variability for available Fe and moderate variability for available Cu, Mn, and Zn in Dasht‐e‐Tabriz soils of Iran.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…In soils of northern Ethiopia, low (for pH) and medium variability (for SOC and available Fe) were reported (Tesfahunegn et al, ). Moderate variability for available Zn, Fe, Cu, and Mn was recorded by Wang, Wu, Liu, Huang, and Fang () in China's paddy growing soils and by Shukla et al (), Shukla et al () in Indian TGP and SHR soils. However, Foroughifar, Jafarzadeh, Torabi, Pakpour, and Miransari () recorded high variability for available Fe and moderate variability for available Cu, Mn, and Zn in Dasht‐e‐Tabriz soils of Iran.…”
Section: Resultsmentioning
confidence: 91%
“…Our finding is similar to the results reported by Shukla et al () who recorded the mean values of 1.66, 1.37, 12.20, and 10.30 mg/kg for available Zn, Cu, Fe, and Mn concentrations, respectively in soils of Indian TGP region. Shukla et al () also reported the mean concentration of 2.24, 1.49, 19.01, and 36.76 mg/kg soil for plant available Zn, Cu, Mn, and Fe, respectively, in the soils of SHR of India. Soil properties exhibited low (only soil pH) to moderate (rest of soil properties) variability with <10, 10 to 100 and > 100% of CV values indicating variability to the extent of low, moderate, and high degree, respectively (Nielsen & Bouma, ).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Even in developed countries, a single soil test for Mo can be expensive. Currently, soil micronutrient mapping (e.g., B and Mo) is performed through chemical analysis of the soil samples [110], which have a very low probability of becoming the basis of precision agriculture based diagnostics. Instead, major technical advances are needed to develop low-cost in situ-based methods to diagnose field level variability in relevant micronutrients (e.g., spectroscopic) ( Table 2), allowing variable-rate micronutrient application to optimize SNF.…”
Section: Available Soil Micronutrientsmentioning
confidence: 99%